Pembuatan Biodiesel dari CPO ALB Tinggi dengan Katalis ZnO Sintesis dari Presipitan ZnCO3 (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Curently, various types of catalysts have been investigated for the production of biodiesel from high FFA feedstock. Crude palm oil (CPO) has a high free fatty acid (FFA) can be usedfor biodiesel production. This research aims to synthesize ZnO catalyst from ZnCO3 presipitation, then it was used for transesterification of CPO has a high FFA to biodiesel. Theeffect of variations in mole ratio of reactants and the amount of catalyst have been studied in order to get yield of biodiesel maximally. FFA content in CPO was 8.36%. Therefore,Biodiesel production was carried out with a two-stage reaction, esterification and transesterification. The esterification reaction was held at temperatures 65oC with H2SO4 catalyst 1% w/w of oil. The transesterification reaction was held at temperatures 65oC with ZnO catalyst. The mole ratio of reactants were 1:6, 1:12, 1:18, ZnO catalyst amount 0.3%, 0.4%, 0.5% and reacton time 60 minutes. The higest yield of biodiesel obtained was 96.03% under condition ratio mole of reactant 1:18 and amount of ZnO catalyst 0.5%. The biodieselhas density 888 kg/m3, viscosity 5.63 mm2/s, flash point 175oC, acid value 0.64 mg-KOH/gbiodiesel and alkyl ester content 98.51%.Keywords: crude biodiesel, crude palm oil, esterification, transesterification, ZnO